A journey longing to get out of poverty - Angel-Daniela Hernandez-Torres; Uriel-Haile Hernandez-Belmonte (ХНУРЕ, 2022)
The aim of this work is to address the travel of the migrants using virtual reality as a medium to expose what the migrants live during their t ravel. The main objective is to perceive and interact with the harsh reality that migrants go through, going from being an observer to becoming a migrant.
Keywords: journey; longing